Respuesta :

Answer:

Step-by-step explanation:

Disclaimer all solutions need to be verified by the student for accuracy in typos, algebra and calculations.

f(x) = x² + 14      g(x) = x - 2      -1 ?   I think it means evaluate when x = -1

Find (f(x) + g(x))  when x = -1

 (f(x) + g(x))  =   [ ( x² + 14)  +  (x - 2)]        insert f(x)  and g(x)

                    =   [ x² + x + 14 - 2]               add like the term

 (f(x) + g(x))  =   x² + x + 12

(f(-1) + g(-1))  =   (-1)² + (-1) + 12             evaluate at x = -1

                   =    1 - 1 + 12

                   =    12